Gastric Follicular Lymphomas Presenting as Subepithelial Tumors: Two Cases - Hyeong Jin Kim; Cheol Woong Choi; Su Bum Park; Su Jin Kim (Yong Chan Lee, 2018)
Follicular lymphoma is the most common form of low-grade B cell lymphoma. Follicular lymphoma occurs predominantly at lymph node sites and rarely in the gastrointestinal tract. Rare gastrointestinal follicular lymphoma is most commonly found in the small intestine, especially in the duodenum, and appears as multiple granules. However, gastric follicular lymphoma mostly appears as a subepithelial tumor. We observed two primary gastric follicular lymphomas that resembled subepithelial tumors located in the body of the stomach. Endoscopic ultrasound revealed hypoechoic lesions located in the submucosa layer. Since endoscopic forceps biopsies were inconclusive, we performed endoscopic submucosal dissection, which resulted in a final pathologic diagnosis of follicular lymphoma. Because of the indolent nature of gastrointestinal follicular lymphoma, the "watch and wait" strategy can be applied in the early phase. The identification of endoscopic characteristics of gastric follicular lymphoma can be helpful for differential diagnosis and decision of treatment strategy. Therefore, we report two cases of primary gastrointestinal follicular lymphoma diagnosed following endoscopic submucosal dissection.